Chapter Ti devo tanto di ciò che sono. Il carteggio tra Claudio Magris e Biagio Marin - BENUSSI, MARIA CRISTINA (Biblioteca di Studi di Filologia Moderna, 2021)
The correspondence between the elderly Biagio Marin and the younger Claudio Magris shows the evolution of an intense relationship from both an emotional and an intellectual point of view. Their letters help us develop the biographies of two writers who occasionally disagreed on personal and cultural grounds. For the poet from Grado, who lost his son, the Germanist was a spiritual heir. However, his Weltanschauung still expressed the proactive values of a generation that had been born before WWI. By contrast, Magris' own values reflected the crisis and anxieties of the twentieth century.